2019
DOI: 10.1590/0102-311x00110218
|View full text |Cite
|
Sign up to set email alerts
|

Iniquidades do ambiente construído relacionado à atividade física no entorno de escolas públicas de Curitiba, Paraná, Brasil

Abstract: Resumo: O objetivo do estudo foi investigar a associação entre as características do ambiente relacionado à atividade física com a renda em áreas de entorno escolar em Curitiba, Paraná. Foram auditados 888 segmentos de rua com um instrumento de observação sistemática em três seções (Rotas, Segmentos e Cruzamentos) no raio de 500 metros ao redor de 30 escolas públicas. O escore total foi a soma das seções. Dados de renda do entorno escolar foram obtidos do Censo Demográfico de 2010, e a distância linear de cada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
0
5
0
7
Order By: Relevance
“…There are some theories to explain adaptative modifications to reduce energy expenditure in low socioeconomic status group 8 . Women in poor neighborhood can face difficulties to engage and keep physically actives 48 . The domestic tasks and care for the other residents of the household are mainly performed by women in Brazil 49 .…”
Section: Discussionmentioning
confidence: 99%
“…There are some theories to explain adaptative modifications to reduce energy expenditure in low socioeconomic status group 8 . Women in poor neighborhood can face difficulties to engage and keep physically actives 48 . The domestic tasks and care for the other residents of the household are mainly performed by women in Brazil 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Fry et al 55 evaluated the availability of Google Street View images in 371 Latin American cities and observed that localities with better socioeconomic conditions tended to have more consistent images. It is worth mentioning that none of the articles selected in this review performed the virtual audit, which, in turn, has been used in previous studies related to the food environment 56 , 57 and physical activity 58 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the micro-scale is differentiated by describing the urban configuration, in terms of presence and quality of infrastructure, such as items measured at the street level (e.g., sidewalks and trees). Individuals’ perception and SSO constitute adequate methods for assessing smaller areas, and information obtained at the micro-scale can contribute to interventions with greater potential for change and lower costs 45 , 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Em Curitiba, um estudo que avaliou a distribuição do ambiente para atividade física nas escolas encontrou piores condições do ambiente em regiões de menor renda e mais distantes do centro, reforçando a ideia de que as periferias das cidades apresentam maiores iniquidades, e por consequência, reforçam um ambiente obesogênico 37 . Entender as características do município torna-se então indispensável para um planejamento de políticas públicas que auxiliem essa população a melhorar suas condições de saúde.…”
Section: Discussionunclassified
“…Por outro lado, a regional Tatuquara tem grande concentração de indústrias, justificando a menor densidade populacional do município. Porém foi a regional com maior variação populacional entre 2010 e 2016, e demonstra grande dependência socioeconômica e dificuldades no acesso a serviços e equipamentos públicos 37 .…”
Section: Discussionunclassified